Activation of Src-family Tyrosine Kinases in hyperproliferative epidermal disorders - Ayli, Elias E. (2008)
BACKGROUND: Src-family tyrosine kinases (SFKs) are important regulators of keratinocyte growth and differentiation. In a broad range of cell types, persistent activation of SFKs correlates with increased cell proliferation. In this study, we determined if SFK activity is increased in cutaneous neoplasia and psoriasis, common hyperproliferative epidermal disorders. METHODS: Formalin-fixed tissue sections of unremarkable epidermis, psoriasis, actinic keratoses, squamous cell carcinoma in situ (SCIS), and squamous cell carcinoma (SCC) were subjected to immunohistochemical staining for activated SFKs. RESULTS: All psoriasis specimens displayed significantly greater staining for activated SFKs than sections of unremarkable skin. In the psoriatic biopsies, the degree of epidermal hyperplasia was proportional to the staining for activated SFKs. All actinic keratoses, SCISs, and SCCs exhibited more prominent staining than sections of unremarkable epidermis. Qualitatively, actinic keratoses displayed weaker staining of activated SFKs than the SCC specimens. No discernable difference in activated SFK staining was seen between in situ and invasive specimens. CONCLUSIONS: This study demonstrates increased staining of activated SFKs in human biopsy specimens of psoriasis and cutaneous neoplasia. These data provide direct evidence for increased activation of SFKs in the pathogenesis of hyperproliferative epidermal disorders.